Range‐wide population size of the lesser prairie‐chicken: 2012 and 2013 - Lyman McDonald; Grant Beauprez; Grant Gardner; Jim Griswold; Christian Hagen; Fawn Hornsby; David Klute; Sean Kyle; James Pitman; Troy Rintz; Doug Schoeling; Bill Van Pelt (Wildlife Society Bulletin)
ABSTRACT We flew aerial line‐transect surveys to estimate the range‐wide population size of lesser prairie‐chickens (Tympanuchus pallidicinctus) in the Great Plains, United States in 2012 and 2013. We also estimated the number of lesser prairie‐chicken leks, the number of mixed‐species leks that contained both lesser and greater prairie‐chickens (T. cupido) and the number of hybrid lesser–greater prairie‐chickens where these species' ranges overlap. The study area included the 2011 estimated occupied lesser prairie‐chicken range in 5 states and was divided into 4 ecoregions. We created a sampling frame over the study area, consisting of 536 15‐ × 15‐km grid cells. We flew 512 transects within a probabilistic sample of 256 cells totaling 7,680 km in 2012 and 566 transects within a probabilistic sample of 283 cells totaling 8,490 km in 2013. We estimated a total of 34,440 individual lesser prairie‐chickens in 2012 (17,615 in 2013) and 350 hybrid lesser–greater prairie‐chickens in 2012 (342 in 2013) in the study area. We estimated a total of 2,930 lesser prairie‐chicken leks in 2012 (2,037 in 2013) and 453 lesser and greater prairie‐chicken mixed leks in 2012 (356 in 2013) in the study area. We discuss the implications of alternative sampling designs with regard to conservation questions to be addressed. © 2014 The Wildlife Society.